2021
DOI: 10.1001/jamanetworkopen.2021.4498
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends and Disparities in Suicidal Behaviors by Sex and Sexual Identity Among Asian American Adolescents

Abstract: This cross-sectional study uses data from the national Youth Risk Behavior Survey to investigate the trends and within-group disparities in 4 suicidal behaviors by sex and sexual identity among Asian American adolescents from 1991 through 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
(109 reference statements)
0
9
0
1
Order By: Relevance
“…En los Estados Unidos desde el año 2011 se ha emitido líneas de prevención del suicidio, dentro de estas estrategias se refuerza la teoría que existe grupos de riesgo como adolescentes y jóvenes (18), grupos discriminados por su orientación sexual, etnias raciales entre otras (19), que dificultan un abordaje adecuado por el estigma cultural que existen en dichos grupos (20); lo cual se puede asemejar a nuestro país donde existe un desentendimiento del gobierno central respecto a salud mental en el abordaje de esta problemática en grupos específicos y esto aún se agrava más cuando los grupos etarios de riesgo sufren de trastornos mentales, discriminaciones, bullying, abandono del estado, etc .…”
Section: Discussionunclassified
“…En los Estados Unidos desde el año 2011 se ha emitido líneas de prevención del suicidio, dentro de estas estrategias se refuerza la teoría que existe grupos de riesgo como adolescentes y jóvenes (18), grupos discriminados por su orientación sexual, etnias raciales entre otras (19), que dificultan un abordaje adecuado por el estigma cultural que existen en dichos grupos (20); lo cual se puede asemejar a nuestro país donde existe un desentendimiento del gobierno central respecto a salud mental en el abordaje de esta problemática en grupos específicos y esto aún se agrava más cuando los grupos etarios de riesgo sufren de trastornos mentales, discriminaciones, bullying, abandono del estado, etc .…”
Section: Discussionunclassified
“…In addition, due to the limitation of data, we were only able to assess suicidal ideation. At the same time, previous studies have suggested that risks and protective factors were associated differently with suicidal ideation and suicide attempts among adolescents (Xiao & Lindsey, 2021a, 2021bXiao & Lu, 2021). To increase the measurement accuracy, validated diagnostic interviews for children and adolescents that assess past and current suicidal ideation and suicide attempts, such as the Kiddie Schedule for Affective Disorders and Schizophrenia (Kaufman et al, 1997;Townsend et al, 2020), the Columbia-Suicide Severity Rating Scale (Posner et al, 2008), and Child Behavior Checklist (Achenbach, 2014), should be adopted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, this is a factor that should not be ignored. When comparing the rate of suicidal attempt and injury by suicidal attempt between the two groups in a study focusing on disparities in suicidal behaviors by sex and sexual identity among Asian American adolescents, there is a clear disparity towards LGBTQ+: with 41% of those that identified as LGBTQ+ attempting suicide compared to 5.5% of the others, and 17.6% of LGBTQ+ participants being injured by suicidal attempts compared to 1.7% of the others [15]. The aforementioned factors should be considered in helping Asian American adolescents against depression.…”
Section: Important Factors That Influence the Depression In Asian Ame...mentioning
confidence: 99%
“…In the past, Asian Americans were documented having very low hospital admission rates, which has also caused many to believe that Asian Americans had low levels of mental health issues [13]. However, this was not the case, as the true depression rates and suicide rates of Asian Americans have been masked by cultural barriers and biases [14][15][16]. It was reported in 2003 that 47% Asian American adolescents experienced depression, while 30% of their European American counterparts had depression issue [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation